Experimental evaluation of high intensity focused ultrasound for fat reduction of ex vivo porcine adipose tissue - Filippou, Antria; Damianou, Christakis A. (My University, 2022)
The present study was stimulated by the continuous growth of commercially available high intensity focused ultrasound (HIFU) systems for fat reduction. Herein, HIFU was utilised for fat ablation using a single-element ultrasonic transducer operating in thermal mode.
Keywords: Adipose; Fat; HIFU; Lipolysis; Porcine; Reduction